A fundamental study on deformation behavior of ski and snow surface - Hashimoto, Y.; Sakanaga, H.; Kagawa, H.; Yoneyama, T.; Nikki, K.; Abe, O. (Science and Skiing VII, 2018)
In order to describe the ski-turn mechanism, the behavior of the ski`s deformation and contact pressure have been measured using deflection sensors and pressure sensors during skiing by skilled skiers (Yoneyama, Kagawa, & Osada, 2010; Yoneyama, Kagawa, & Tatsuno, 2012). It is important to understand the mechanical characteristics of the snow surface for analysis of the results and development of skis. We examined the hardness of the snow surface using rigid indenters, and experimentally revealed the influence of the hardness, temperature, density, and grain size of snow (Hashimoto et al., 2015). From the results, the indent shape could be estimated after a rigid indenter was pressed to a homogeneous snow surface. However, the deformation behavior in an elastic plate—such as skis—is still not well understood. In this study, elastic plates with constant thickness were indented to a snow surface. Then the relationship between the snow hardness and the shapes of the elastic plate and the indent on snow surface were considered.